Awareness And Usage of Digital Payment Services Among Senior Citizen in Kanyakumari District - C. Aslin Liola Lins; B. Nalatha Vijilin (Frontiers in Health Informatics, 2026)
Digital payments are one of the most important concepts, and make prospects for Cashless Economy in India. Financial literacy and awareness about digital payments is paramount in India to make the cashless economy. Nearly 26% of India has internet access, and there are only 200 million users of digital payment services. This study is mainly based on the survey research. Simple random and multi stage stratified random sampling technique has used. It is based on well-structured questionnaire which was conducted to study the awareness and usage of senior citizens towards digital payments services. The questionnaires were distributed to 50 respondents in different occupation and different banks in Kanyakumari District. The data were collected by using a well-structured questionnaire which contains type of digital payment services availed by senior citizens, frequency of usage of digital payments services and awareness about digital payments services. Primary data were collected with the help of questionnaire from 50 respondents of the Kanyakumari District. Secondary data were collected with the help of online sources, journals and reports. The important awareness of digital payments services among the senior citizens who belong to secondary school level are easy and save time and transparency and accountability. Among the senior citizens who belong to primary school level, the important awareness of digital payments services are transparency and accountability and safety. Educational status wise there is a significant difference in the awareness of digital payments services among the senior citizens, are identified in the case of easy and save time, convenience, lower risk, secure privacy, control black money, control the corruption, transparency and accountability, safety, prompt settlement, increase Govt. Income and other benefits.